没有针轮的摆线变速机 - 李远庆 (Jixie chuandong)
In a cycloidal reducer, pin wheels are composed by precision components such as the pin wheel housing, a gear pin and outer casing. After exploring to the linear of a cycloid curve, the regular pattern of the normal movement is found, and a derivation of the cycloid normal mechanism is designed. Thus, various types of cycloid and its isometric curve are able to be created or processed, only by using a general cylindrical milling cutter and a grinding wheel to feed and cut the normal lead screw. Therefore, it is possible to manufacture the internal and external gear with a simple rolling mesh. Subsequently, a pinwheel which was formed by a number of components ranging from tens to hundreds could be replaced by a single internal gear. Moreover, a cycloidal reductor without pinwheels can be produced, which will result in a remarkable improvement of the efficiency of the reducer. The maximum reduction ratio of a single lever can be increased from 87 to more than 200.